2008
DOI: 10.1001/jama.299.21.2533
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Between Patient-Predicted and Model-Predicted Life Expectancy Among Ambulatory Patients With Heart Failure

Abstract: EART FAILURE ACCOUNTS DIrectly for 55 000 deaths and indirectly for an additional 230 000 deaths in the United States each year. 1 Despite advances in care, the prognosis for patients with symptomatic heart failure remains poor, with median life expectancy of less than 5 years. 2 For those with the most advanced disease, 1-year mortality rates approach 90%. 3,4 About half of these deaths are due to progressive pump failure, while the remainder are sudden. 5 Prognosis is highly dependent on a multitude of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
160
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(164 citation statements)
references
References 46 publications
4
160
0
Order By: Relevance
“…[8][9][10][11][12][13] The future is often narrowly construed as related to prognosis, and several studies focus on preferences for how and when prognosis is communicated. 12,14 The literature on adjusting to chronic illness generally focuses on the psychological and biomedical consequences of positive or negative adjustment, rather than how perceptions of illness or changing health influence perceptions of the future.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] The future is often narrowly construed as related to prognosis, and several studies focus on preferences for how and when prognosis is communicated. 12,14 The literature on adjusting to chronic illness generally focuses on the psychological and biomedical consequences of positive or negative adjustment, rather than how perceptions of illness or changing health influence perceptions of the future.…”
Section: Introductionmentioning
confidence: 99%
“…However, interviews of patients with advanced HF and their care providers identified that patients did not recall receiving material about their condition nor did they feel involved in the decision-making process about their illness (17). Furthermore, studies (28,29) have shown that there is poor patient and physician congruity regarding advanced care preferences and that the goal of therapy may change over time. Data from the HF cohort in the Study to Understand Prognoses and Preferences for Outcomes and Risks of Treatments (SUPPORT) (30)(31)(32) reported that up to one-third of inpatients would have desired a discussion of treatment preferences and end-of-life care had they been given the opportunity by their care providers.…”
Section: Communicationmentioning
confidence: 99%
“…1 Similarly, it is not clear whether patients suffering from heart failure actually appreciate the seriousness of their condition. 2 Heart failure has a devastating effect on an individual's quality and length of life, and patients are at risk of sudden death from fatal arrhythmias. 3 Studies have shown that almost half of all deaths in patients with heart failure are sudden.…”
Section: Introductionmentioning
confidence: 99%
“…This poor prognosis is often not appreciated by the patient or the physician and even when the physician is aware, there may be reluctance in informing patients of this poor prognosis unless directly asked about it. 2 The inception of the heart failure nurse specialist (HFN) and hospital-based heart failure clinic has led to a number of potential interactions with different healthcare professionals for patients in a variety of settings. Some have a view that the HFN might be better equipped to deal with informing patients of the nature and poor prognosis of heart failure rather than the clinician looking after the patient as they have more frequent interactions with the patient and generally build a better rapport with them.…”
Section: Introductionmentioning
confidence: 99%